EVALUATING THE EFFECTIVENESS OF THE OPTICAL-ELECTRONIC SURVEILLANCE SYSTEM - Borovik, O. V.; Rachok, R. V.; Darmoroz, M. M. (Radio Electronics, Computer Science, Control, 2017)
Context. In the protection of the state border of Ukraine used the new system of optical-electronic observation (SOEO). However, its potential is not fully realized. One of the reasons for this is the lack of scientific and methodological apparatus of evaluation of the effectiveness of its functioning in various factors of natural and technogenic character. The latter makes it relevant to conduct appropriate research. Objective. The aim of this work is to develop a methodology for assessing the efficiency of SOEO. Method. The proposed indicators of efficiency of functioning of individual surveillance technology and their integrated use with one tower system opto-electronic surveillance. The work also proposed a new indicator of efficiency of functioning of system of optical-electronic observation. The indicator takes into account features of conducting observations with the comprehensive use of various technical means of border protection in various conditions of natural and technogenic character, and given the terrain. Substantiation of expediency of their application involved the use of probabilistic-statistical methods. Results. On the basis of information about digital characteristics of the topography of the investigated area carried out determining unobservable areas, the so-called “dead zones”. The proposed method of calculating the index of efficiency of functioning of system of opticalelectronic observation. The description of algorithmic and software implementation of this technique. Using the developed software the analysis of the functioning of the current system optical-electronic surveillance, identified key problematic aspects and directions of improving the efficiency of SOEO. Conclusions. Modern building of SOEO is not optimal. Possible directions of increase of efficiency of its functioning can be optimization of the placement of the towers system on the ground, adjusting the height placement on the towers of surveillance technology and a good selection of the technical means of observation